Novel research model for in vitro immunotherapy: co-culturing tumor organoids with peripheral blood mononuclear cells - Peng Li; Minli Huang; Yifan Ma; Yongbin Zhang; Changhong Shi (Cancer Cell International)
Abstract Tumor organoids have emerged as powerful tools for in vitro cancer research due to their ability to retain the structural and genetic characteristics of tumors. Nevertheless, the absence of a complete tumor microenvironment (TME) limits the broader application of organoid models in immunological studies. Given the critical role of immune cells in tumor initiation and progression, the co-culture model of organoids and peripheral blood mononuclear cells (PBMCs) may provide an effective platform for simulating the interactions between immune and tumor cells in vitro. This model stands as a robust instrument for dissecting the TME, elucidating the molecular interactions, and exploring the therapeutic applications of chimeric antigen receptor (CAR)-engineered lymphocytes, as well as other cancer treatment modalities. This review systematically evaluates the advantages and disadvantages of the co-culture model, identifies its technical bottlenecks, and proposes corresponding optimization strategies. By summarizing the latest research advancements in this co-culture model, our goal is to provide valuable insights for further model optimization and clinical application, thereby promoting immunological research and bridging the gap between experimental outcomes and clinical practice.